Computational-guided determination of the functional role of 447-52D long CDRH3. Issue 12 (30th April 2019) - Kamau, Edwin; Bonneau, Richard; Kong, Xiang-Peng
Abstract: 447-52D (447) is a human monoclonal antibody that recognizes a conserved epitope in the crown region of the third variable loop (V3) of HIV-1 gp120, and like many anti-HIV-1 antibodies with broad neutralization capabilities, it has a long heavy-chain complementarity determining region (CDRH3). Here, we use a combination of computational mutagenesis and modeling in tandem with fluorescence polarization assays to interrogate the molecular basis of 447 CDRH3 length and the individual contribution of selected CDRH3 residues to affinity. We observe that 447 CDRH3 length provides a large binding surface area and the best enthalpic contributions derived from hydrophobic packing, main-chain hydrogen bonds, electrostatic and van der Waals interactions. We also found out that CDRH3 residue Try 100I is critical to 447 binding affinity.